(untitled) - Kelts, Roland (New York, 2006)
May the G-force be with you -- Atom boys -- The business of anime -- Toy story -- Japan’s IP problem -- Strange transformations -- Cosplay and otakudom : the draw of DIY -- Future shocks -- Anime appeals.
Keywords: Popular culture,Phổ biến văn hóa; Japan,Nhật Bản